Histologic comparison of the uterine pathologic effects of erythropoietin and U-74389G - Constantinos Tsompos; Constantinos Panoulis; Constantinos Zografos; GeorgeC Zografos; Apostolos Papalois (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2026)
Background: This manuscript compared the effects at uterine pathology (UP), after processing with either the drug erythropoietin hormone (Epo), or the lazaroid antioxidant agent (L) one U-74389G. This comparison was provided by outcomes of 2 preceding branches.Objective: Both studies estimated the effect, after each drug use in a planned uterine ischemia -  reperfusion (UIR) mice experimental setting.Methods: Both principal experiment timepoints, the uterine histology was evaluated were the min 60th after reperfusion (A, C, E groups) and also the min 120th after reperfusion (B, D, F groups). Along, A & B groups were placebo, C & D groups were processed by Epo and E & F groups after the L process.Results: The one study-branch of Epo has presented a hardly significant recessing potency for the total UP within the “lesion-free” grade alteration by -0.0916667 [-0.1907629 - 0.0074296] (p-values = 0.0583). However, the other study-branch of U-74389G presented a respective non-significant accentuation of the total UP within the “lesion-free” grade alteration by 0.2229748 [-0.1376592 - 0.5836089] (p-value = 0.4940). Both branch studies got co-evaluated as they belong to a common experiment. Their outcome was that Epo seems to ameliorate the UP status, whereas L seems to deteriorate it; however, their discrepancy seems to be non-significant (p-value = 0.0677).Conclusion: There is a slight non-significant superiority of Epo than L in UIR pathology restoration (p-value = 0.0677), possibly useful in several clinical situations.